Epidemiology of influenza B/Yamagata and B/Victoria lineages in South Africa, 2005-2014. - Mpho Seleka; Florette K Treurnicht; Stefano Tempia; Orienka Hellferscee; Senzo Mtshali; Adam L Cohen; Amelia Buys; Johanna M McAnerney; Terry G Besselaar; Marthi Pretorius; Anne von Gottberg; Sibongile Walaza; et al. (PLoS ONE, 2017)
BACKGROUND:Studies describing the epidemiology of influenza B lineages in South Africa are lacking. METHODS:We conducted a prospective study to describe the circulation of influenza B/Victoria and B/Yamagata lineages among patients of all ages enrolled in South Africa through three respiratory illness surveillance systems between 2005 and 2014: (i) the Viral Watch (VW) program enrolled outpatients with influenza-like illness (ILI) from private healthcare facilities during 2005-2014; (ii) the influenza-like illnesses program enrolled outpatients in public healthcare clinics (ILI/PHC) during 2012-2014; and (iii) the severe acute respiratory illnesses (SARI) program enrolled inpatients from public hospitals during 2009-2014. Influenza B viruses were detected by virus isolation during 2005 to 2009 and by real-time reverse transcription polymerase chain reaction from 2009-2014. Clinical and epidemiological characteristics of patients hospitalized with SARI and infected with different influenza B lineages were also compared using unconditional logistic regression. RESULTS:Influenza viruses were detected in 22% (8,706/39,804) of specimens from patients with ILI or SARI during 2005-2014, of which 24% (2,087) were positive for influenza B. Influenza B viruses predominated in all three surveillance systems in 2010. B/Victoria predominated prior to 2011 (except 2008) whereas B/Yamagata predominated thereafter (except 2012). B lineages co-circulated in all seasons, except in 2013 and 2014 for SARI and ILI/PHC surveillance. Among influenza B-positive SARI cases, the detection of influenza B/Yamagata compared to influenza B/Victoria was significantly higher in individuals aged 45-64 years (adjusted odds ratio [aOR]: 4.2; 95% confidence interval [CI]: 1.1-16.5) and ≥65 years (aOR: 12.2; 95% CI: 2.3-64.4) compared to children aged 0-4 years, but was significantly lower in HIV-infected patients (aOR: 0.4; 95% CI: 0.2-0.9). CONCLUSION:B lineages co-circulated in most seasons except in 2013 and 2014. Hospitalized SARI cases display differential susceptibility for the two influenza B lineages, with B/Victoria being more prevalent among children and HIV-infected persons.